A Short Sixteenth-Century Catalogue of Scholastic Sentences Commentaries in Vat. Lat. Lat. 3919 - Ledsham, Cal (Bulletin de Philosophie Médiévale, 2021)
Abstract This article contains an edition of a list of authors of Sentences commentaries in Vatican City, BAV, Cod. Vat. Lat. 3919, which is similar to one found in the 1535 Quentel edition of Denys the Carthusian's texts. This manuscript version is thus a primary text indicating the content of a (Germanic) library in the early 1500's, and showing how sixteenthcentury editors took library lists and both homogenized and regularized their attribution, orthography and chronology. The names listed are identified against modern lists and their variation against that 1535 edition noted, the provenance and date of the list established and not readily-identifiable names are discussed.